English Shortened Words on TVShows Title - Pradnya Paramita Dewi (Journal of English Language Teaching and English Linguistics, 2022)
This study deals with the English word-formation process that focuses on word shortening: clipping, blending, acronyms, and abbreviations. Furthermore, this study is aimed at identifying the word types, creation, and development as well as the meaning of the new shortened words, the most shortened words produced, and the reasons for creating shortened words as vocabulary development. This study uses a qualitative research design to describe the study's problems. The data are in the form of TV show titles for the last fifteen years, which use shortened words. The program was aired between 2005-2020 on TV channels and Streaming Media Services. The data are presented in the form of a table. The results of the study show that the creation and the development of shortened words are varied, with the most productive form being an abbreviation, followed by the other forms, namely blending, clipping, and acronym, respectively. There are various types of shortened words in each form. Some reasons are identified for making the words shorter. 1). It is more efficient and saves time in speaking; 2). It is more interesting and eye-catching; 3). Reducing the mispronounced words. In conclusion, shorter TV show title with unique creations can help the audiences remember them easily